What numbers to choose for my lottery ticket? Behavior anomalies in the Chinese online lottery market - Jieyao Ding (Max Planck Institute for Research on Collective Goods, 2011)
The Chinese Online Lottery provides field evidence of three anomalies. The first anomaly, which has previously not been documented when there is a financial incentive to overcome, is the guidance effect. Since the target game in this project is a pari-mutuel game, which means people will share the jackpot with other winners, the best strategy should be to choose the least popular numbers among others - information that people could obtain on the webpage. However, to my surprise, instead of doing so, people would choose the most popular numbers among others. The second anomaly tested is the gambler's fallacy. Although it is proved that the gambler's fallacy does exist, the influence lasts only three days, which is much shorter than prior research. Furthermore, the dataset's availability makes it possible to show how the two fallacies unfold over time within a round. This was unlikely before the phenomenon of online betting. The result demonstrates that later entrants are subject to more fallacies than earlier ones. Finally, the paper adds to the evidence showing the additional, culturally contingent pull of special numbers. In China, bettors prefer to choose the lucky number 8, even it won the game in prior rounds, but they are reluctant to choose the unlucky number 14 even it has not been picked for a long while.
Keywords: C93; D81; 330; Lottery Game; Gambler's Fallacy; Guidance Effect; Number Culture; Glücksspiel; Internet; Verhaltensökonomik; Soziale Norm; China